CXCR4-Directed Imaging in Solid Tumors - Werner, Rudolf A.; Kircher, Stefan; Higuchi, Takahiro; Kircher, Malte; Schirbel, Andreas; Wester, Hans-Jürgen; Buck, Andreas K.; Pomper, Martin G.; Rowe, Steven P.; Lapa, Constantin (Frontiers in Oncology, 2019)
Despite histological evidence in various solid tumor entities, available experience with CXCR4-directed diagnostics and endoradiotherapy mainly focuses on hematologic diseases. With the goal of expanding the application of CXCR4 theranostics to solid tumors, we aimed to elucidate the feasibility of CXCR4-targeted imaging in a variety of such neoplasms. Methods: 19 patients with newly diagnosed, treatment-naïve solid tumors including pancreatic adenocarcinoma or neuroendocrine tumor, cholangiocarcinoma, hepatocellular carcinoma, renal cell carcinoma, ovarian cancer, and prostate cancer underwent [68Ga]Pentixafor PET/CT. CXCR4-mediated uptake was assessed both visually and semi-quantitatively by evaluation of maximum standardized uptake values (SUVmax) of both primary tumors and metastases. With physiologic liver uptake as reference, tumor-to-background ratios (TBR) were calculated. [68Ga]Pentixafor findings were further compared to immunohistochemistry and [18F]FDG PET/CT. Results: On [68Ga]Pentixafor PET/CT, 10/19 (52.6%) primary tumors were visually detectable with a median SUVmax of 5.4 (range, 1.7 – 16.0) and a median TBR of 2.6 (range, 0.8 – 7.4), respectively. The highest level of radiotracer uptake was identified in a patient with cholangiocarcinoma (SUVmax, 16.0; TBR, 7.4). The relatively low uptake on [68Ga]Pentixafor was also noted in metastases, exhibiting a median SUVmax of 4.5 (range, 2.3 – 8.8; TBR, 1.7; range, 1.0 – 4.1). A good correlation between uptake on [68Ga]Pentixafor and histological derived CXCR4 expression was noted (R=0.62, P<0.05). In the 3 patients in whom [18F]FDG PET/CT was available, [68Ga]Pentixafor exhibited lower uptake in all lesions. Conclusions: In this cohort of newly diagnosed, treatment-naïve patients with solid malignancies, CXCR4 expression as detected by [68Ga]Pentixafor-PET/CT and immunohistochemistry was rather moderate. Thus, CXCR4-directed imaging may not play a major role in the management of solid tumors in the majority of patients.